Improvement of the physical, mechanical and thermal insulation properties to produce gypsum boards by using waste materials - A.Ali, Faiza; H. Abd- Allah, Hamed; H.Mari, Baraa (Iraqi Journal of Science, 2023)
In this paper, a study of improving the physical properties, mechanical and thermal insulation are conducted to produce gypsum boards with lightweight from waste materials. These boards can be used as an internal packaging wall or partitions tile of non-Bering with a high thermal insulation. Gypsum plaster mixed with waste material like (PET Polyethylene terephthalate, sawdust in size4.75mm and rubber) in different ratio (5%, 7%, 10%, 15%, 20%, 25%and 30%) of plaster to produce boards and then to find out the effect of these materials on the properties of boards, so that tests of consistency, setting time, flexural strength, density and thermal conductivity were achieved for all samples to find out this effect. The result shows that the best additive ratio to produce gypsum board with best physical, mechanical, and low thermal conductivity is 5,7% of PET.